A Methodology to Compare Biomechanical Simulations With Clinical Brain Imaging Analysis Utilizing Two Blunt Impact Cases - Tan, X. Gary; Sajja, Venkata Siva Sai Sujith; D’Souza, Maria M.; Gupta, Raj K.; Long, Joseph B.; Singh, Ajay K.; Bagchi, Amit (Frontiers in Bioengineering and Biotechnology, 2021)
According to the US Defense and Veterans Brain Injury Center (DVBIC) and Center for Disease Control and Prevention (CDC), mild traumatic brain injury (mTBI) is a common form of head injury. Medical imaging data provides clinical insight into tissue damage/injury and injury severity, and helps medical diagnosis. Computational modeling and simulation can predict the biomechanical characteristics of such injury, and are useful for development of protective equipment. Integration of techniques from computational biomechanics with medical data assessment modalities (e.g., magnetic resonance imaging or, MRI) has not yet been used to predict injury, support early medical diagnosis or assess effectiveness of personal protective equipment. This paper presents a methodology to map computational simulations with clinical data for interpreting blunt impact TBI utilizing two clinically different head injury case studies. MRI modalities, such as T1, T2, Diffusion weighted imaging (DWI) - Apparent diffusion coefficient (ADC), were used for simulation comparisons. The two clinical cases were reconstructed using finite element analysis to predict brain deformation based on medical reports documented by clinician. The clinical imaging findings are mapped to the simulation results using image based clinical analyses of head impact injuries, and modalities that could capture simulation results has been identified. In case 1, the MRI results showed lesions in the brain with skull indentation, while case 2 had lesions in both coup and contrecoup sides with no skull deformation. Simulation data analyses show that different biomechanical measures and thresholds are needed to explain different blunt impact injury modalities; specifically, strain rate threshold corresponds well with brain injury with skull indentation, while minimum pressure threshold corresponds well with coup-contrecoup injury; and DWI has been found to be most useful modality for MRI data interpretation. As the findings from these two cases are substantiated with additional clinical studies, this methodology can be broadly applied as a tool to support injury assessment in head trauma events and to improve countermeasures (e.g., diagnostics, protective equipment design) to mitigate these injuries.